PENGARUH PEMAHAMAN PAJAK, PELAYANAN PAJAK DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PREFERENSI RISIKO PERPAJAKAN SEBAGAI VARIABEL MODERASI - Nurul Amanda Putri Ansari; Putri Intan Permata Sari; Nelly Prima Putri (Ensiklopedia of Journal, 2026)
The purpose of this study was to determine the effect of tax understanding, tax services, and tax sanctions on taxpayer compliance with tax risk preferences as a moderating variable. This study uses objects on taxpayers registered at the tax service office (KPP) Pratama Solok. The sample in the study consisted of 100 individual taxpayer respondents at KPP Pratama Solok who were determined using the Slovin formula. Data analysis using descriptive statistical tests and multiple linear regression tests with the help of SPPS 26 tools.This study proves that tax understanding, tax services and tax sanctions have a significant positive effect on taxpayer compliance, and tax risk preferences are able to moderate tax understanding, tax services, and tax sanctions on taxpayer compliance.